Gain‐improved double‐slot LTSA with conformal corrugated edges. Issue 8 (31st May 2017) - Liu, Ya‐Qiao; Liang, Jian‐Gang; Wang, Ya‐Wei
Abstract: In this article, a novel double‐slot linearly tapered slot antenna with conformal corrugated edges, is proposed. By using double‐slot structure, the E ‐plane aperture field of the proposed antenna is more like a plane wave, which helps to improve the directivity of the antenna. Meanwhile, a novel corrugated edge is designed. This conformal corrugated edge can cover all the outer edges of the antenna which has a better improvement of the impedance bandwidth compared with the rectangle corrugated edge. Additionally, according to the theory of microwave network, this article analyzes the reason of bandwidth enhancement realized by double‐slot structure. The proposed antenna provides 145% fractional bandwidth from 3.5 GHz to 22 GHz. The gain of the proposed antenna is more than 12 dB from 6.5 GHz to 21 GHz, and more than 8 dB at the whole operating band.